EFFECTS: an expanded access program of everolimus for patients with subependymal giant cell astrocytoma associated with tuberous sclerosis complex - Fogarasi, Andras; Witt, Olaf (BMC neurology, 2016)
Background Everolimus, a mammalian target of rapamycin (mTOR) inhibitor, has been shown to be effective and safe in the treatment of subependymal giant cell astrocytoma (SEGA) associated with tuberous sclerosis complex (TSC). The Everolimus For Fast Expanded aCcess in TSC SEGA (EFFECTS) study was designed to provide everolimus access to patients with SEGA associated with TSC and to mainly assess the safety and also efficacy of everolimus in a real-world setting. Methods EFFECTS was a phase 3b, open-label, noncomparative, multicenter, expanded access study. Eligible patients were ≥ 3 years of age, with a definite diagnosis of TSC, and with at least one SEGA lesion identified by MRI or CT scan. Patients received once daily everolimus (dose adjusted to attain a trough level of 5-15 ng/mL). Safety evaluation was the primary objective and included collection of adverse events (AEs) and serious AEs, with their severity and relationship to everolimus. Efficacy evaluation, which was the secondary objective, was based on the best overall response as per medical judgment. Results Of the 120 patients enrolled, 100 (83.3 %) completed the study. Median age of patients was 11 years (range, 1-47). Median daily dose of everolimus was 5.82 mg (range, 2.0-11.8). Median duration of exposure was 56.5 weeks (range, 0.3-130). The overall incidence of AEs was 74.2 %. Aphthous stomatitis (18 [15.0 %]), pyrexia (18 [15.0 %]), bronchitis (11 [9.2 %]), and stomatitis (10 [8.3 %]) were the most common AEs reported. Overall, 25 patients had grade 3 AEs; most frequent was stomatitis (4 [3.3 %]). Grade 4 AEs were reported in three (2.5 %) patients. A total of 62 (51.7 %) patients had suspected drug-related AEs, of which 15 (12.5 %) were of grade 3 or 4. In eight (6.7 %) patients, AEs led to drug discontinuation. With regard to efficacy, 81 (67.5 %) patients had a partial response, 35 (29.2 %) had a stable disease, and one (0.8 %) had progressive disease. The response was unknown in three (2.5 %) patients. Conclusion This study confirms the acceptable safety profile of everolimus in patients with SEGA associated with TSC in a real-world setting. The results further support the efficacy of everolimus in the treatment of SEGA associated with TSC. (EudraCT: 2010-022583-13)
Gesehen am 22.03.2018